2020 family medicine postgraduate examinations at The University of the West Indies: successes and challenges in the time of COVID-19 pandemic. Issue 1149 (26th May 2021) - Motilal, Shastri; Paul-Charles, Joanne; Asnani, Monika; Khan, Raveed; Ricketts-Roomes, Tana; Pinder-Butler, Sabriquet; Herbert, Joseph; Farquharson, Carnille; Conliffe, Catherine; Standard-Goldson, Aileen; Smith, Kristen; Morris, Euclid; et al.
ABSTRACT: Little has been published regarding postgraduate assessments during the COVID-19 pandemic. There is an urgent need to graduate well-trained specialists including family physicians who play a key role in patient care. The successes and challenges encountered in mounting qualifying 2020 Family Medicine examinations during the COVID-19 pandemic at the University of the West Indies are described in this paper. Human resource, planning, use of technology and virtual environments are discussed, which enabled successful examinations at this multicampus regional site.